Poor glycemic control and its predictors among people living with diabetes in low- and middle-income countries: a systematic review and meta-analysis - Abere Woretaw Azagew; Chilot Kassa Mekonnen; Mark Lambie; Thomas Shepherd; Opeyemi O. Babatunde (BMC Public Health)
Abstract Introduction Variability in blood glucose remains a challenge in diabetic management. Therefore, this review aimed to estimate the overall poor glycemic control and identify its predictors among people living with diabetes in low- and middle-income countries (LMICs). Methods The authors searched articles in PubMed, Embase, OVID, CINAHL Plus, Cochrane Library, PsychInfo, Google, and Google Scholar. The search results were exported to the Rayyan software to check their eligibility. The Newcastle–Ottawa scale was used to assess the study quality. Stata version 17 was used for analysis. A random effect model was computed. Heterogeneity was assessed by the Cochrane Q test and I-squared (I2). The funnel plot asymmetry test and/or Egger’s regression test (p < 0.05) were used to detect the publication bias. Then it was treated by the trim and fill analysis. The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO) with the reference number CRD42023430175. Results In total, forty-nine articles were used. Of which forty-five articles with 15,981 participants were used for pooled prevalence estimation. The pooled prevalence of poor glycemic control among people living with diabetes in LMICs was found to be 69.06% (95% CI: 65.66–72.46), I2 = 96.1%, p < 0.001). Alcohol intake (AOR = 2.07: 95% CI: 1.27–3.36), poor adherence to dietary recommendations (AOR = 3.16, 95% CI: 1.13–8.85), poor adherence to anti-diabetic medication (AOR = 2.85, 95% CI: 1.04 -7.85), diabetic complications (AOR = 1.37, 95% CI: 1.00–1.88), and co-morbid conditions (AOR = 1.98, 95% CI: 1.28–30.07) were found to be predictors of poor glycemic control. Conclusions The pooled prevalence of poor glycemic control was significantly high in LMICs. Drinking alcohol, poor adherence to dietary recommendations, poor adherence to anti-diabetic medication, diabetes complications, and co-morbid conditions were found to be the determinants of poor glycemic control among people living with diabetes. Tight glycemic control strategies have been implemented to achieve optimal blood glucose. Further research on the regional and contextual factors influencing glycemic control would be recommended.